A Comparative Clinical Study of Ultrasonography-Guided Perivascular and Perineural Axillary Brachial Plexus Block for Upper Limb Surgeries - Vastrad, Vinuta Vidyanand (Anesth Essays Res, 2019)
BACKGROUND: Axillary brachial plexus block (ABPB) is safest among other methods of brachial plexus block because of its ease and reliability. The two approaches of ultrasonography-guided ABPB are perivascular (PV) and perineural (PN). AIMS: This study was conducted to compare primary outcomes such as performance time, onset of the block, number of needle passes, block success rate, duration of sensory and motor block, and complications between ultrasound-guided PV and PN ABPB in patients posted for upper limb surgeries. SETTINGS AND DESIGN: This prospective randomized study was conducted on 106 patients American Society of Anesthesiologists Class I and II posted for forearm, wrist, and hand surgeries, who were allotted into Group PV and Group PN 53 each. MATERIALS AND METHODS: In both methods, 20 mL of the drug was used. To start with, musculocutaneous nerve was blocked with 5 mL of the drug. In the PV technique, remaining 15 mL of the drug was deposited anterior and posterior to axillary artery, and in PN technique, 5 mL of the drug was injected around radial, ulnar, and median nerve. STATISTICAL ANALYSIS: Mann–Whitney and Chi-square test were used for statistical analysis. RESULTS: Significant difference was observed between the two groups in performance time (PV – 8.647 ± 0.54 min and PN – 14.53 ± 0.20 min), onset time (PV – 19.48 ± 2.83 min and PN – 13.86 ± 1.81 min), and number of needle passes (PV – 2.30 ± 0.50 and PN – 4.91 ± 0.66). Other parameters were comparable in both the groups. CONCLUSIONS: Ultrasound-guided PV axillary plexus block is better than PN axillary plexus block with respect to performance time and number of needle passes; but onset time was shorter in PN block, with precaution eliminating the risk of complications.